Numerical analysis of bridge girder with composite dowel shear connection = Analiza numeryczna dźwigara mostowego z zespoleniem typu ?compisite dowels? - Lacki, Piotr; Nawrot, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work presents a brief description of VFT-WIB? steel-concrete composite beams, examples of composite dowel shear connection shapes are presented. A steel-concrete bridge girder construction solution for the new shape of composite dowel shear connection was proposed.
Keywords: bridge girder; steel-concrete composite beams; composite dowels; VFT-WIB? beams; dźwigar mostowy; belki zespolone stalowo-betonowe; zespolenie composite dowels; belki VFT-WIB?